2001
DOI: 10.1177/104973230101100305
|View full text |Cite
|
Sign up to set email alerts
|

Caring and Expressions of Spirituality by Urban Caregivers of People with Stroke in African American Families

Abstract: Expressions of spirituality by urban caregivers in African American families are the focus of the study discussed in this article. Data presented here were collected as part of a larger study that examined these caregivers' experience and meaning of caring as they influenced their capacity to care for people with stroke within their family systems. This study was executed within and supported the framework of systemic organization by Friedemann, according to which families as open systems strive for well-being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Overall, current findings support assertions in the literature regarding the importance of religion and spirituality for African American caregivers (Dilworth-Anderson et al, 2002Farran, 1999Farran, , 2003Mbanaso et al, 2006;Pierce, 2001) and provide a more specific understanding of how they operate in the lives of older caregivers within this population. In particular, results from this study reveal the special role that attention to the spiritual rewards of caregiving may have in decreasing caregiver stress, enhancing external and internal supports, and providing a buffer against should maintain awareness that these factors impact individual caregivers differently; there is no one pattern for all older African American caregivers-or caregivers in general.…”
Section: Implications For Social Work Practice and Researchsupporting
confidence: 78%
See 1 more Smart Citation
“…Overall, current findings support assertions in the literature regarding the importance of religion and spirituality for African American caregivers (Dilworth-Anderson et al, 2002Farran, 1999Farran, , 2003Mbanaso et al, 2006;Pierce, 2001) and provide a more specific understanding of how they operate in the lives of older caregivers within this population. In particular, results from this study reveal the special role that attention to the spiritual rewards of caregiving may have in decreasing caregiver stress, enhancing external and internal supports, and providing a buffer against should maintain awareness that these factors impact individual caregivers differently; there is no one pattern for all older African American caregivers-or caregivers in general.…”
Section: Implications For Social Work Practice and Researchsupporting
confidence: 78%
“…This study identified four major ways religious or spiritual beliefs were helpful by providing: (a) the strength to endure (45%), (b) a sense of duty and reciprocity toward those who had cared for them (24%), (c) faith for encouragement and inspiration (24%), and (d) gratification that fostered positive feelings about giving care (7%). In another qualitative study of urban African American caregivers, Pierce (2001) found spirituality interwoven in eight themes of caregiving, including filial ethereal value, self-contemplation, motivation for a philosophical introspection, filial piety, living in the moment and hope for the future, purpose, motivation based on approval from care recipient, and Christian piety.…”
Section: Religious Involvement and Spiritual Rewards Of Caregivingmentioning
confidence: 97%
“…Caregivers reported not only suffering in their caregiving experience but also positive aspects such as personal growth, appreciation for life, and an improved relationship with the stroke survivors. Studies among the western caregivers found that caregiving was also regarded as self-contemplation, through which they were able to find the intrinsic goodness of caregiving when looking within themselves (Pierce, 2001). Caregivers also voiced a sense of determination or purpose, a strong spiritual connectedness and spiritual growth in caregiving (Pierce, 2001).…”
Section: Dynamic Meanings In Caregivingmentioning
confidence: 99%
“…Studies among the western caregivers found that caregiving was also regarded as self-contemplation, through which they were able to find the intrinsic goodness of caregiving when looking within themselves (Pierce, 2001). Caregivers also voiced a sense of determination or purpose, a strong spiritual connectedness and spiritual growth in caregiving (Pierce, 2001). Research findings in other illness experiences such as dementia also illustrated that caregivers displayed resilience in caregiving (Yu et al, 2018) as they found motivations and meanings (Quinn, Clare, & Woods, 2010) and gained a sense of mastery, greater family cohesion, and marital satisfaction through caregiving (Yu et al, 2018).…”
Section: Dynamic Meanings In Caregivingmentioning
confidence: 99%
“…In one study of urban African American caregivers, Pierce (2001) found spirituality interwoven in several themes of caregiving, two of which touched on motivational aspects. First, caregiving itself was noted as an impetus for philosophical reflection concerning vulnerability; faith in God made the vulnerability experienced through caregiving tolerable.…”
Section: Literature Reviewmentioning
confidence: 98%